RSSDI textbook of diabetes mellitus - Tripathy, BB; Chandalia, HB; Das, AK; Rao, PV; Madhu, SV; Mohan, V (New Delhi, India : Jaypee Brothers Medical Publishers, 2012)
In the course of the last few decades, India has emerged as the country with the highest number of patients with deabetes. In keeping withthis, in india diabetology has emerged as a major specialty in the practice of both general medicine and endocrinology. Over the last thirty years, several centers have adpted diabetes as a single disease specialty for the state of the art investigations and clinical care.
CONTENTS VOLUME 2 SECTION 9: COMORBID CONDITIONS SECTION 10: COMPLICATIONS SECTION 11: DIABETES THROUGH LIFE AND EVENTS SECTION 12: LIVING WITH DIABETES SECTION 13: HEALTH CARE DELIVERY SECTION 14. PREVENTION
Incluye appendix, index
Keywords: DIABETES; DIABETES MELLITUS; DIABETES CLINIC